Lymphoma diagnostics: getting more from less. (19th February 2019) - Galardy, Paul J.; Bedekovics, Tibor; Macintyre, Elizabeth; Miles, Rodney R.
Summary: In the modern era, clinicians and pathologists increasingly make challenging diagnoses in patients with suspected lymphoma using minimal amounts of diagnostic material. The increase in utilization of minimally invasive procedures, such as fine needle aspiration or needle core biopsies, lead to challenges in our ability to make accurate histopathological assessments of disease, including the integration of new diagnostic and prognostic testing, with smaller amounts of material. The trend towards minimally invasive diagnostics is also often in conflicting interest with researchers seeking to study tissue specimens to better understand the biology and genetics of these diseases to move the field forward. Thankfully, there are emerging fields which seek to extract large amounts of diagnostic and prognostic data out of material that is circulating in the blood of patients with lymphoma. Here we will review recent exciting data regarding the use of circulating tumour cells, circulating tumour DNA, and the detection and utility of circulating exosomes and how it can assist in diagnosis, prognosis and therapeutic monitoring. These advances hold the promise to enable continued safe patient care while also advancing discovery, translational and clinical research.